The Role of Local and International Non-governmental Organizations in the Development of Pakistan: Examining EDHI Center as a Case Study - AHMAD, ARSLAN (İstanbul Kültür Üniversitesi, 2024)
NGOs, or Non-Governmental Organizations, operate without profit motives, focusing on volunteerism and community service to address development issues. In Pakistan, they fill gaps left by government efforts, especially in marginalized areas, where the EDHI Foundation is a prominent example known for its humanitarian work. Founded by Abdul Sattar EDHI, it provides crucial support regardless of boundaries, leveraging agility to respond swiftly to societal needs. In Pakistan, NGOs, categorized as International, National, and Local, play crucial roles in addressing societal challenges. This study examines NGO governance, legitimacy, and accountability in Pakistan, using Labaree's typology to structure the literature review. The EDHI Foundation serves as a case study. The EDHI Foundation's multifaceted humanitarianism in Pakistan includes extensive ambulance services, 350 units in major cities, 5,191 shelter homes, dignified funeral services, langar provisions, and 89 schools providing free education to 16,143 students annually. In conclusion, NGOs like the EDHI Foundation significantly impact Pakistan's socio-economic landscape by addressing diverse challenges. Their holistic approaches, spanning emergency response, social welfare, healthcare, and education, demonstrate the transformative potential of dedicated NGOs in uplifting communities and fostering compassion. The EDHI Foundation's commitment exemplifies the positive change NGOs can bring and their ability to serve as pillars of support in addressing societal needs.
Pakistan'ın Kalkınmasında Yerel ve ​​Uluslararası Sivil Toplum Kuruluşlarının Rolü: EDHI Center'ın Örnek Olarak İncelenmesi
Yüksek lisans tezi.
Keywords: Non-Government Organizations; NGOs; EDHI Center; International NGOs